Role of membrane shape in regulating the phosphatidylinositol cycle at contact sites. (July 2019) - Bozelli, José Carlos; Epand, Richard M.
Highlights: Membrane shape changes modulate DGKε activity and substrate acyl chain specificity. ER-plasma membrane junctions provide sites where membrane shape could be altered. Actin polymerization could provide the mechanical force needed for membrane shape changes at contact sites. The regulation of DGKε by membrane shape couples lipid transfer with the DAG kinase step of the PI-cycle. The regulation of the properties of DGKε contributes to the rate and specificity of the entire PI cycle. Abstract: The extensive number of metabolic processes regulated by phosphatidylinositol (PI) phospholipids highlights their physiological importance. The major metabolic pathway for their biosynthesis in cells is the PI-cycle. Contrary to most metabolic cycles, reactions of the PI-cycle occur in two different locations; those are, the plasma membrane (PM) and endoplasmic reticulum (ER). Lipid movement between the two organelles is, therefore, a requirement of the cyclical process. Moreover, in mammals the PI-cycle yield PI molecular species enriched in specific acyl chains, namely 1-stearoyl-2-arachidonoyl acyl chains. Hence, to ensure cycle efficiency and specificity it should take place in specialized regions of PM and ER rather than being randomly distributed among those membranes. Along these lines, ER-PM contact sites have emerged as the location where a number of proteins related to the PI-cycle have been reported to localize. Of importance to this review is the presence of the epsilon isoform of diacylglycerol kinase (DGKε) at ER-PM contact sites. In the PI-cycle DGKε is in part responsible for the acyl chain enrichment of the PI molecular species. However, it has recently been shown that the enzyme can only engage in the PI-cycle upon membrane morphological changes. In this review we will discuss the PI-cycle at ER-PM contact sites and how the generation of membrane negative Gaussian curvature nearby those regions could regulate the cycle. We will focus our discussion on the hypothesis that actin polymerization provides the mechanical force needed to change membrane shape nearby ER-PM contact sites, which will transiently trigger DGKε and, therefore, link enzymatic catalysis and lipid transfer in the PI-cycle.